Indicadores de qualidade de água nos reservatórios Acarape do Meio e Gavião - Lima, Gustavo Ross Ribeiro (2019)
Uncertainty about access to acceptable quality water, especially for human supply, defines the critical scenario currently faced by water management entities. Several factors significantly contribute to aggravate such situation, especially those related to anthropic actions. The Brazilian semiarid tropic, found in much of the northeastern backcountry, has some peculiarities that intensify water scarcity, such as high temperatures, low rainfall and high evaporation rates. In view of this, there is an urgent need to execute strategic plans and monitoring programs in order to preserve the reservoirs used and increase the guarantee margin of the service offered. Eutrophication, a very common phenomenon in lentic systems, is characterized by nutrient accumulation and consequent increase in primary productivity. To determine the trophic degree of a particular aquatic body, the Trophic State Index (EIT) is used, using concentration values ​​basically of phosphorus and chlorophyll a. Another widely used index is the Water Quality Index (WQI), which quantifies water quality based on several parameters. The present work aimed to evaluate the quality indicators and indices, as well as their relationships, in the Acarape do Meio and Gavião reservoirs. From the monitoring data of the two reservoirs considered, the modified Trophic State Index for the semiarid tropic (IETMSA) was developed. This index contains usual parameters in the representation of the degree of trophy (total phosphorus and total nitrogen), excludes Secchi disc depth and considers the total cyanobacterial count. The IETMSA showed a good correlation with the different EIT models (0.888 ≤ r ≤ 0.922). The total cyanobacterial count (CB) in both reservoirs was estimated through chlorophyll a and the nutrients total phosphorus and total nitrogen. Nonlinear multiple regression explained 85.2% of the semiannual variation of CB. For water quality analysis, three indices were adapted and used: IQANSF, IQAR and IQACCME. In the use of IQACCME, parameters were pre-selected (CB, CTT, OD and pH) and t-selected (PT and SDT). Relevant association was obtained between the different EIT models and the IQAR (0.735 ≤ r ≤ 0.829). Despite this apparent relationship, the two indices serve different purposes.